The F plasmid conjutome: the repertoire of E. coli proteins translocated through an F-encoded type IV secretion system - Abu Amar M. Al Mamun; Kimberley Kissoon; Yang Grace Li; Erin Hancock; Peter J. Christie (mSphere, 2024)
ABSTRACT Bacterial conjugation systems pose a major threat to human health through their widespread dissemination of mobile genetic elements (MGEs) carrying cargoes of antibiotic resistance genes. Using the Cre Recombinase Assay for Translocation (CRAfT), we recently reported that the IncFV pED208 conjugation system also translocates at least 16 plasmid-encoded proteins to recipient bacteria. Here, we deployed a high-throughput CRAfT screen to identify the repertoire of chromosomally encoded protein substrates of the pED208 system. We identified 32 substrates encoded by the Escherichia coli W3110 genome with functions associated with (i) DNA/nucleotide metabolism, (ii) stress tolerance/physiology, (iii) transcriptional regulation, or (iv) toxin inhibition. The respective gene deletions did not impact pED208 transfer proficiencies, nor did Group 1 (DNA/nucleotide metabolism) mutations detectably alter the SOS response elicited in new transconjugants upon acquisition of pED208. However, MC4100(pED208) donor cells intrinsically exhibit significantly higher SOS activation than plasmid-free MC4100 cells, and this plasmid carriage-induced stress response is further elevated in donor cells deleted of several Group 1 genes. Among 10 characterized substrates, we gained evidence of C-terminal or internal translocation signals that could function independently or synergistically for optimal protein transfer. Remarkably, nearly all tested proteins were also translocated through the IncN pKM101 and IncP RP4 conjugation systems. This repertoire of E. coli protein substrates, here termed the F plasmid “conjutome,” is thus characterized by functions of potential benefit to new transconjugants, diverse TSs, and the capacity for promiscuous transfer through heterologous conjugation systems.IMPORTANCEConjugation systems comprise a major subfamily of the type IV secretion systems (T4SSs) and are the progenitors of a second large T4SS subfamily dedicated to translocation of protein effectors. This study examined the capacity of conjugation machines to function as protein translocators. Using a high-throughput reporter screen, we determined that 32 chromosomally encoded proteins are delivered through an F plasmid conjugation system. The translocated proteins potentially enhance the establishment of the co-transferred F plasmid or mitigate mating-induced stresses. Translocation signals located C-terminally or internally conferred substrate recognition by the F system and, remarkably, many substrates also were translocated through heterologous conjugation systems. Our findings highlight the plasticity of conjugation systems in their capacities to co-translocate DNA and many protein substrates.